2001
DOI: 10.1079/phn2001215
|View full text |Cite
|
Sign up to set email alerts
|

Dietary guidelines for pregnant women

Abstract: The nutrition of pregnant women is decisive in the course of gestation and the health of both mother and child. However, in the Spanish population, clinical monitoring of nutrition is rare, the control of bodyweight receiving most attention. Many studies show that pregnant women take too much fat and too little carbohydrate, and that intakes of fibre and several trace elements are lower than recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 9 publications
(36 reference statements)
0
18
1
1
Order By: Relevance
“…According to our findings, a nonnegligible proportion of women in our study population did not achieve the minimum daily recommended intake of vegetable, ;200 g/d (31), and this was associated with less favorable birth outcomes in our study. It would be desirable, from a public health point of view, to reinforce preconceptional as well as prenatal nutritional counseling, in the context of healthier habits, to encourage pregnant women to eat adequate daily amounts of vegetables (apart from potatoes) in accordance with current recommendations.…”
Section: Discussioncontrasting
confidence: 53%
“…According to our findings, a nonnegligible proportion of women in our study population did not achieve the minimum daily recommended intake of vegetable, ;200 g/d (31), and this was associated with less favorable birth outcomes in our study. It would be desirable, from a public health point of view, to reinforce preconceptional as well as prenatal nutritional counseling, in the context of healthier habits, to encourage pregnant women to eat adequate daily amounts of vegetables (apart from potatoes) in accordance with current recommendations.…”
Section: Discussioncontrasting
confidence: 53%
“…Other food items that were assessed but not listed in the table are mutton, pork trotters, organ meats, nuts, fruit, rice, bread, oil, herbal tea, tea, coffee and wine/alcohol; for percentages of other columns ('same as before' and 'do not usually eat'), please refer to Supplementary Table 2. in the study could be due to modern dietary advice that promotes milk products as good sources of Ca and other nutrients (15) . Insufficient Ca intake during pregnancy may lead to lower Ca content in the fetus' skeleton (15) . Tea and coffee intakes were decreased in all three ethnic groups, likely as a consequence of the reported negative effects of caffeine on pregnancy outcomes (17,18) .…”
Section: Discussionmentioning
confidence: 99%
“…Not only is higher energy intake recommended during the second half of the pregnancy, a higher increment in intakes of various nutrients including protein, Ca, folate, vitamin C and vitamin D is recommended during pregnancy (15) . Increasing the consumption of nutrient-dense fruit and vegetables and lowering the intake of foods with low nutrient density are thus advised during pregnancy (15) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other hand, Jacobs, Andersen, and Blomhoff (2007) reported that whole-grain consumption is associated with a reduced risk of noncardiovascular, noncancer death attributed to inflammatory diseases in the Iowa women's health study. Ortega (2001) indicated that the nutrition of pregnant women is decisive in the course of gestation and the health of both mother and child, and recommended 7-8 portions of cereals and legumes per day.…”
Section: Pulses and Cardiovascular Diseasesmentioning
confidence: 99%